Mối quan hệ giữa các khía cạnh của sự hài lòng tiền lương đến sự cam kết tổ chức, lòng trung thành: Trường hợp nhân viên xe buýt tại thành phố Hà Nội - Nguyễn Danh , Nam; Uông Thị Ngọc, Lan (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
The study aims to explore the relationships among dimensions of pay satisfaction on organisational commitment and loyalty of employees at bus enterprises in Hanoi city. Survey data were collected from 432 employees at 7 bus enterprises under Transerco. Findings from the structure equation model (SEM) indicated that the dimensions of pay satisfaction had a significant direct impact on multidimensional organizational commitment, while the facets of organisational commitment were found to have a significant impact on their attitude and behavioural loyalty. The results also found an impact between attitude loyalty and behavioural loyalty. As a result, the authors put forward some implications for managers of Hanoi bus enterprises to focus on improving pay satisfaction and organisational commitment to improving employee loyalty in the coming time.